Effectiveness of Motivational Intervention Based on Mind Set on Academic Procrastination and Learned Helplessness - maryam sanami; ali taghvaeinya; fariborz nikdel (مطالعات روانشناسی تربیتی)
The purpose of this study was to the effectiveness of motivational intervention based on mind set on academic procrastination and learned helplessness of students.The research method was quasi-experimental with pretest-posttest design and control group. Statistical population included all high school girls’ students of the first secondary in Rustaq city of Fars Province in 2022. Measurement tools included Learned Helplessness Scale (1988) and the Academic Procrastination Questionnaire (1984). The first, three school selected randomly, consequently 40 students that scored above the cut-off point convenient sampling were selected and randomly assigned two experimental and control group. In the later step, the students in the experimental group received motivational intervention based on change set mind for 8 session of 90 minutes and the control group did not receive any intervention. The study’s data were analyzed using multivariate analysis of covariance with SPSS23. Findings indicated motivational intervention based on mind set significantly decreased academic procrastination and learned helplessness in comparison to the control group (p <0.01). May concludes that the motivational intervention based on mind set in has been effective in reducing academic procrastination and learned helplessness. The findings of this research emphasize the importance of paying attention to teaching based on mind set on decreased academic procrastination and learned helplessness in students.